2014
DOI: 10.1039/c4md00007b
|View full text |Cite
|
Sign up to set email alerts
|

Machine-assisted synthesis of modulators of the histone reader BRD9 using flow methods of chemistry and frontal affinity chromatography

Abstract: Novel technologies were developed and used for the synthesis and evaluation of new triazolopyridazine BRD9 inhibitors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
33
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 43 publications
(34 citation statements)
references
References 27 publications
0
33
0
1
Order By: Relevance
“…Several BRD9-dircted efforts in discovery chemistry have been reported, [1115] developing chemotypes for BRD9-specific engagement. A recent study further suggested BRD9 as a dependency in acute myeloid leukemia (AML), where bromodomain inhibition prompted a cytostatic response.…”
mentioning
confidence: 99%
“…Several BRD9-dircted efforts in discovery chemistry have been reported, [1115] developing chemotypes for BRD9-specific engagement. A recent study further suggested BRD9 as a dependency in acute myeloid leukemia (AML), where bromodomain inhibition prompted a cytostatic response.…”
mentioning
confidence: 99%
“…A similar approach has been followed in most systems reported to date, in which self-optimization has been implemented. These systems cover different areas of chemistry: polymerization reaction [13 ,14 ], heterogeneous catalytic processes [1,2,5], droplet formation [15,16] assembly of nanoparticles [17] and even multi-step syntheses [4,[18][19][20][21]. As we shall show below, this approach to automation is readily extendable to include chemoinformatics and design of experiments, using data exchange standards, such as OPC.…”
Section: Hardware For Self-optimization Of Closed-loop Systems Labwarementioning
confidence: 98%
“…Highly homologous bromodomain containing protein 7 (BRD7) is a component of the SWI/SNF polybromoassociated BAF (PBAF) complex and has been proposed as a tumor suppressor [30]. Within the last year, there have been several publications focussing on BRD9 and dual BRD7/9 chemical probe development [31][32][33].…”
Section: Brd7 and Brd9mentioning
confidence: 99%